Effect of manual, preloaded, and automated preloaded injectors on corneal incision architecture after IOL implantation. Issue 10 (October 2020) - Cennamo, Michela; Favuzza, Eleonora; Salvatici, Maria Cristina; Giuranno, Gabriele; Buzzi, Matilde; Mencucci, Rita
Abstract : The CO2 -powered and preloaded delivery systems with the depth guard nozzle ensured less trauma to the wound and contributed to preserving the endothelial side of the incision even during the implantation of high-power IOLs, compared with the manual injector. Abstract : Purpose: To analyze the effects on corneal morphology of manual, preloaded, and automated preloaded intraocular lens (IOL) injectors in eye bank human corneas by environmental scanning electron microscopy (ESEM) and in patients after phacoemulsification using anterior segment optical coherence tomography (AS-OCT). Settings: Eye Clinic, Careggi University Hospital, Florence, Italy. Design: Retrospective and experimental study. Methods: Seventy-eight corneal incisions were examined after IOL implantation: 30 in human corneas mounted on an artificial chamber using ESEM (ex vivo); 48 in patients undergoing phacoemulsification (in vivo). Three different injectors were used for both analyses: manual (Monarch III, n = 26), manual preloaded (UltraSert, n = 26), and automated preloaded system (AutonoMe, n = 26). Thirty IOLs were implanted in the ex vivo study: 5 intermediate and 5 high dioptric powers for AcrySof IQ (Monarch and UltraSert) and for Clareon (AutonoMe) IOLs. In the in vivo analysis, 16 corneal wounds for each injector were evaluated using AS-OCT; in the ex vivo study, incision width was measured and Descemet membrane detachment, posterior wound retraction, and posterior gape were analyzed. Results: In the eye bank corneas, the incision width was significantly wider in the high dioptric power IOL manual subgroup ( P < .05), with more Descemet tearing compared with AutonoMe. In the in vivo study, the incidence of Descemet membrane detachment, posterior gape, and wound retraction was lower in the automated preloaded group at 1 postoperative day 1. Conclusions: The automated preloaded injector ensured less trauma to the wound and contributed to preserving the endothelial side of the incision even during the implantation of high-power IOLs and in the early postoperative period.